KHF2: A Mild and Selective Desilylating Agent for Phenol tert-Butyldimethylsilyl (TBDMS) Ethers - Lakshman, Mahesh K.; Tine, Fatou A.; Khandaker, Tashrique A.; Basava, Vikram; Agyemang, Nana B.; Benavidez, Michael S. A.; Gaši, Marikone; Guerrera, Lisa; Zajc, Barbara (Synlett, 2017)
TBDMS (t-BuMe2Si, tert-butyldimethylsilyl) ethers of a variety of phenols have been deprotected with KHF2 in MeOH, at room temperature. Carboxylic ester and labile phenolic acetate were unaffected under these conditions. In competition reactions between TBDMS ethers of a phenol and two primary benzylic alcohols, the phenolic ether underwent cleavage whereas the alcohol ethers remained intact. From a substrate containing both a phenolic hydroxyl group and a secondary, doubly benzylic hydroxyl group protected as TBDMS ethers, the phenol was rapidly and selectively released. Cleavage of TBDMS, TBDPS, and TIPS ethers of a phenol was also compared. TBDMS and TBDPS ethers underwent cleavage at room temperature within 30 minutes, whereas removal of the TIPS ether required 2.5 hours. Ease of cleavage appears to be TBDMS ≈ TBDPS > TIPS. At 60 °C, TBDMS ethers of primary benzylic, allylic, and unactivated alcohols can be efficiently desilylated over a prolonged period (13–17 h). Thus, KHF2 proves to be a mild and effective reagent for the selective desilylation of phenol TBDMS ethers at room temperature.
Keywords: deprotection; desilylation; silicon; fluoride; potassium bifluoride